Waste management: regulations and problems in Kansas - Joseph P. Harner; James P. Murphy (Kansas Agricultural Experiment Station Research Reports, 1992)
The dairy industry is receiving greater pressure to reduce its potential pollution to the environment. As the demand grows for cleaner streams, dairy operations will need to reduce and control the nutrient and sediment loading of the runoff leaving the farm vicinity. Existing dairy operations will need to evaluate the impact of manure storage and management on the environment. Costs of controlling the runoff must be weighed against new lot construction in an alternate location. Future dairy facilities will need to address current regulations and be designed for compliance with future and more stringent regulations.; Dairy Day, 1992, Kansas State University, Manhattan, KS, 1992;
Keywords: Dairy Day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-131-S; Waste management; Kansas regulations; Manure production